2004
DOI: 10.1007/bf02968043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sensitivity to 5-FU on the basis of thymidylate synthase (TS)/dihydropyrimidine dehydrogenase(DPD) activity and chromosomal analysis in micro tissue specimens of breast cancer

Abstract: TS mRNA showed a positive correlation with TS activity, suggesting that this method of using small amounts of tissue can replace anti-cancer drug sensitivity tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…FdUMP and the folate cofactor 5-10-methylene tetrahydrofolate bind to TS to form a covalently-bound ternary complex that inhibits TS [32] . The expression level of TS among tumors varies considerably, and cellular sensitivity to 5-FU is related to alterations in the TS level [33] . In our study, insulin/5-FU treatment increased the level of the TS ternary complex and decreased the free TS expression compared with 5-FU treatment in the Ls-174-t cells.…”
Section: Discussionmentioning
confidence: 99%
“…FdUMP and the folate cofactor 5-10-methylene tetrahydrofolate bind to TS to form a covalently-bound ternary complex that inhibits TS [32] . The expression level of TS among tumors varies considerably, and cellular sensitivity to 5-FU is related to alterations in the TS level [33] . In our study, insulin/5-FU treatment increased the level of the TS ternary complex and decreased the free TS expression compared with 5-FU treatment in the Ls-174-t cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thymidylate synthase (TS) is an important enzyme for DNA synthesis and the target for 5-FU. Previous clinical studies have demonstrated that TS expression level predicts the response to 5-FU-based chemotherapy [8][9][10]. Moreover, patients with node-positive breast cancer with high TS expression demonstrated the most significant benefit of adjuvant 5-FU-containing chemotherapy.…”
Section: Introductionmentioning
confidence: 94%
“…One complicating factor is that the mRNA and protein activity levels do not necessarily coincide. For example, analysis of biopsies from breast cancer specimens revealed no correlation between DPD mRNA and DPD activity in tumor tissue (r 5 0.139, P 5 0.4423) [Ota et al, 2004].…”
Section: à3mentioning
confidence: 99%